Uso de estrato vertical por pequenos mamíferos em floresta de galeria e cerradão no sudoeste do Brasil - Lopes, Wellington Hannibal (2009)
Studies on vertical stratification of small mammals in the Cerrado biome are scarce and, therefore, this study has the aim to check the community composition of small mammals in relation to the vertical stratum utilization in gallery forest and cerradão of south-western Brazil. The captures were carried out during the months of August/September, November/December 2006 and February/March, May/June 2007. The traps were set in three transaction lines with 10 capture stations each one. Each station had a trap on the ground, other in the understory (2.0 to 3.0 m in height) and another in the canopy (8 to 10 m) in each environment, totalling 60 stations.. With an effort of 3600 traps-night 11 species of small mammals were captured, which were distributed differentially regarding the environments and the utilization of the vertical strata. Species presented habitat high segregation on physiognomies, only Rhipidomys macrurus presented in two environments. As for use of vertical strato for the Correspondence analysis Caluromys philander was the only notable in the canopy, Cryptonanus agricolai, Marmosa murina and, Oecomys bicolor were in the understory, and Gracilinanus agilis and Nectomys rattus were only sampled on the ground. In relation the faunistic and environments parameters formed two groups, where C agricolai and G. Agilis were associated to cerradão, dry season and number of tree and C. philander, M. Murina, N. rattus and O. bicolor were associated to gallery forest, stratification, number of branch and lianas. The Cerrado biome presents distinct fauna of small mammals associated with the two main forest physiognomies in it: gallery forest and cerradão. The utilization of traps in different strata increased the species richness, showing that they are distributed in different vertical strata of the forest, utilizing the complexity of the environment which enables them to coexist.